2018
DOI: 10.1007/s10123-018-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected disinfectants efficiency against Listeria monocytogenes biofilm formed on various surfaces

Abstract: Listeria monocytogenes is a main etiological factor of listeriosis, spread mainly by food products. In recent years, an increasing number of patients with listeriosis and an augmentation in L. monocytogenes antibiotic resistance, e.g. to penicillin and ampicillin, has been reported. The aim of the study was to characterise the L. monocytogenes strains isolated from fish-processed food products. Species identification, based on the multiplex-PCR reaction, was performed, and the genetic similarity of the isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of L. monocytogenes isolates was confirmed by PCR reaction. Two pairs of primers L1 (5′-CAG CAG CCG CGG TAA TAC-3′), L2 (5′-CTC CAT AAA GGT GAC CCT-3′), LM1 (5′-CCT AAG ACG CCA ATC GAA-3′) and LM2 (5′-AAG CAC TTG CAA CTG CTC-3′; Oligo.pl) were applied [ 22 ]. The PCR reaction mixture (25 μL) included 1× PCR buffer (Promega, Madison, WI, USA), 2 mM MgCl 2 (ABO, Gdańsk, Poland), 1.25 mmol dNTPs (Promega, Madison, WI, USA), 0.5 μM of each primer (Oligo.pl), 1 unit of Taq DNA polymerase (Promega, Madison, WI, USA), ultrapure water and DNA isolated from L. monocytogenes .…”
Section: Methodsmentioning
confidence: 99%
“…The identification of L. monocytogenes isolates was confirmed by PCR reaction. Two pairs of primers L1 (5 -CAG CAG CCG CGG TAA TAC-3 ), L2 (5 -CTC CAT AAA GGT GAC CCT-3 ), LM1 (5 -CCT AAG ACG CCA ATC GAA-3 ) and LM2 (5 -AAG CAC TTG CAA CTG CTC-3 ; Oligo.pl) were applied [22]. The PCR reaction mixture ( The PCR products were analyzed by agarose gel electrophoresis (1.5% agarose) stained with Midori Green (NIPPON Genetics EUROPE GmbH, Düren, Germany) in 1× TBE (Tris-boran-EDTA) buffer (BioRad, Hercules, CA, USA) using a DNA size standard (GeneRuler™ 1000 bp DNA Ladder; Fermentas, Waltham, MA, USA)-conditions 90 V, 1 h.…”
Section: Species Identificationmentioning
confidence: 99%
“…Following the 24 h test period, a 100 μl aliquot of each well was transferred to 100 μl of Dey-Engley Neutralizing Broth (Sigma-Aldrich, St. Louis, MO, United States) and allowed to incubate for 2 minutes at room temperature. A 100 μl aliquot was then spread onto the surface of a MH agar plate and incubated at 37°C for 18–24 h (Skowron et al, 2018). The MBC was designated as the lowest biocide concentration which resulted in no viable growth of that isolate.…”
Section: Methodsmentioning
confidence: 99%